2013
DOI: 10.1038/nchembio.1278
|View full text |Cite|
|
Sign up to set email alerts
|

A serine-substituted P450 catalyzes highly efficient carbene transfer to olefins in vivo

Abstract: Genetically encoded catalysts for non-natural chemical reactions will open new routes to sustainable production of chemicals. We designed a unique serine-heme ligated cytochrome “P411” that catalyzes efficient and selective carbene transfers from diazoesters to olefins in intact Escherichia coli cells. The mutation C400S in cytochrome P450BM3 gives a signature ferrous-CO Soret peak at 411 nm, abolishes monooxygenation activity, raises the resting state FeIII/II reduction potential, and significantly improves N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
325
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(356 citation statements)
references
References 30 publications
(33 reference statements)
8
325
0
10
Order By: Relevance
“…While creating a version that could function inside of a cell, utilizing endogenous reductant NADPH, we discovered that the identity of the ironligating amino acid residue (which is always Cys in P450s) is very important: Ser- (Coelho et al 2013b) and His-ligated (Wang et al 2014a) enzymes are easily generated and are much better cyclopropanation catalysts. Of course, these mutations obliterate the P450's native monooxygenase activity; they also shift the characteristic Soret peak at 450 nm.…”
Section: New Enzymes From Old: Adding To the Cytochrome P450's (Alreamentioning
confidence: 99%
See 1 more Smart Citation
“…While creating a version that could function inside of a cell, utilizing endogenous reductant NADPH, we discovered that the identity of the ironligating amino acid residue (which is always Cys in P450s) is very important: Ser- (Coelho et al 2013b) and His-ligated (Wang et al 2014a) enzymes are easily generated and are much better cyclopropanation catalysts. Of course, these mutations obliterate the P450's native monooxygenase activity; they also shift the characteristic Soret peak at 450 nm.…”
Section: New Enzymes From Old: Adding To the Cytochrome P450's (Alreamentioning
confidence: 99%
“…Both labs have now demonstrated that optimized cyclopropanating enzymes catalyze tens of thousands of turnovers for various olefins, with substrate range and product selectivity that are tunable by protein engineering (Bordeaux et al 2015;Coelho et al 2013b). The P450-derived enzyme functions very well in whole bacterial cells, where a His-ligated variant has been used for preparative-scale synthesis of a pharmaceutical intermediate (Wang et al 2014a).…”
Section: New Enzymes From Old: Adding To the Cytochrome P450's (Alreamentioning
confidence: 99%
“…Engineered heme proteins such as cytochrome P450 enzymes, myoglobin, and cyctochrome C have emerged as excellent catalysts for new‐to‐nature reactions,1, 2 including carbene‐transfer reactions such as cyclopropanations,3, 4, 5, 6, 7 olefinations, and8, 9 N−H,10, 11 Si−H,12 and B−H insertion reactions 13. These enzymes have proven amenable to optimization by both genetic methods and co‐factor replacement 14, 15, 16, 17, 18, 19, 20.…”
mentioning
confidence: 99%
“…The discovery [6][7][8] and engineering [9][10][11] of enzymes fueled by the formidable development in high-throughput biotechnology has allowed for tailored manufacturing of materials [12], medicines [13], and fine chemicals [14]. However, developing the full potential of biocatalysis and synthetic biology is dependent on exploring hitherto novel biochemistries [4,15] and reaction mechanisms [16] that expand the catalytic capabilities currently found in nature [15].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, collectively known as "promiscuity" [18], presumably allows for an increased fitness of the organism through the evolution of novel catalytic functions. Some prominent examples include the α,β-hydrolase fold [19] that is capable of harnessing 17 different reaction mechanisms [20], P450 monooxygenase-catalyzed cyclization [21], cyclopropanation [14], and γ-humulene synthase that generates 52 different natural products starting from the same polyisoprene substrate [22]. As accelerating promiscuous activities through enzyme engineering constitutes a cornerstone for expanding the catalytic scope of enzymes [15], an enhanced fundamental understanding of the molecular mechanisms underpinning the evolution of the catalytic function is desired.…”
Section: Introductionmentioning
confidence: 99%